Eight Weeks of Physical Training Decreases 2 Years of DNA Methylation Age of Sedentary Women - da Silva Rodrigues, Guilherme; Noma, Isabella Harumi Yonehara; Noronha, Natália Yumi; Watanabe, Lígia Moriguchi; da Silva Sobrinho, Andressa Crystine; de Lima, João Gabriel Ribeiro; Sae-Lee, Chanachai; Benjamim, Cicero Jonas Rodrigues; Nonino, Carla Barbosa; Bueno, Carlos Roberto (Research quarterly for exercise and sport, 2024)
Purpose: The acceleration of epigenetic age is a predictor of mortality and contributes to the increase in chronic diseases. Adherence to a healthy lifestyle is a strategy to reduce epigenetic age. The present study aimed to determine whether eight weeks of combined (aerobic and strength) training (CT) can influence the epigenetic age of women between 50 and 70 years old and the differences in sites and methylated regions. Methods: Eighteen women (AAR Low : lower age acceleration residual, n = 10; AAR High : higher age acceleration residual, n = 8) participated in a combined exercise training program (60 minutes, 3× a week) for eight weeks. DNA was extracted from whole blood using the salting out technique. DNA methylation was performed using the array technique (Illumina's Infinium Methylation BeadChip 850k). We used the DNA Methylation Age Calculator platform to calculate the biological epigenetic age. Two-way ANOVA followed by FISHER LSD posthoc was Applied, adopting p < .05. Results: After eight weeks of CT, there were no changes to the epigenetic age acceleration for the AAR Low group (PRE: −2.3 ± 3.2 to POST: −2.3 ± 3.6). However, the AAR High group significantly decreased the age acceleration (PRE: 3.6 ± 2.6 to POST: 2.2 ± 2.7) (group effect, p = .01; time effect, p = .31; group vs. time effect, p = .005). Conclusion: CT for eight weeks benefits the epigenetic clock of women with the most accelerated age.